The Effects of Human Relations on Employee Performance a Case Study of Baklim Foundation Limited Mbarara Western Uganda - Sharon Agumenaitwe (Agumenaitwe Sharon, 2023)
The purpose of this study was to investigate the impact of human relations on employee performance, with a focus on Baklim Foundation Limited, located in Mbarara city, Western Uganda. The study aimed to address three specific objectives: to assess the effect of communication on employee performance, to evaluate the influence of conflict resolution on employee performance, and to explore the impact of collaboration on employee performance. A cross-sectional survey research design was employed, utilizing a quantitative research approach. A sample of 40 respondents was selected from the organization using simple random sampling. Data collection was conducted through questionnaires, and the analysis was performed using descriptive statistics, correlation and multiple regression analyses. The findings also revealed the significant effect of communication, collaboration and conflict resolution on the performance of employees at Baklim Foundation Limited. Finally, the study recommended that BFL and other organizations should focus more on implementing fair conflict resolution mechanisms, open and flexible communication channels and assign some work to employees in groups to encourage collaboration with in the organization.